STUDI EVALUASI EFEKTIVITAS PELAKSANAAN PRAKTIK PENGALAMAN LAPANGAN (PPL) MAHASISWA PROGRAM STUDI BIMBINGAN DAN KONSELING FKIP UNTAN PONTIANAK TAHUN 2017 - Purwanti Purwanti; Abas Yusuf (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2018)
This study aims to evaluate the effectiveness of the implementation of Field Experience Practice (PPL) for Student Guidance and Counseling Study Program FKIP UNTAN Pontianak 2017 The method used is Descriptive with the form of survey research. The evaluation technique used is CIPP (contetx, input, process, product). The population of 2017 PPL participants was 49 people. Data collection tools used are questionnaires with structured questionnaires with open questions and interviews if there is a questionable questionnaire result. Research results in general implementation of PPL in schools has been effective even though it has not been maximized. The results of context evaluation have been very good, BK teachers in most schools have been very good. The results of context evaluation are very effective, which means that students have been carefully prepared by the institution to implement PPL. Process evaluation is in the category of quite effective because there are still many schools that do not provide class schedules for BK activities and the opportunity to practice in some schools is still lacking. Evaluation of results in conditions is very effective because the value of students gets more